Bariatric patient from the point of view of a nutritionist - Sikorska, Hanna; Kucharczuk, Magda; Juraszek, Karolina; Wyżgowski, Przemysław; Leksowski, Krzysztof (Journal of Education, Health and Sport, 2019)
Nowadays obesity is one of the biggest worldwide problem. The predominant factor that may result in obesity is an excesive amount of energy and low physical activity. At the present time there are two overwhelming methods to fight obesity- conservative treatment and bariatric surgery. The second one is regarded as the most effective way to reduce body weight of the people suffering from the morbid obesity. Surgical treatment can only be efficient when it is followed by introducing dietary indications, both before and after the surgery. The bariatric patients have to be monitored by medical staff including the dietician to help them change eating habits. The dietician’s support is also crucial to avoid nutrient deficiency and digestive system ailments.